2015
DOI: 10.1063/1.4936334
|View full text |Cite
|
Sign up to set email alerts
|

The effect of residual gas scattering on Ga ion beam patterning of graphene

Abstract: The patterning of graphene by a 30 kV Ga+ focused ion beam (FIB) is studied by in-situ and ex-situ Raman spectroscopy. It is found that the graphene surrounding the patterned target area can be damaged at remarkably large distances of more than 10 μm. We show that scattering of the Ga ions in the residual gas of the vacuum system is the main cause of the large range of lateral damage, as the size and shape of the tail of the ion beam were strongly dependent on the system background pressure. The range of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…Since graphene is very sensitive to irradiation from ion and electron beams, [32,[44][45][46][47] it is important to ensure that the FIB, EBID and ALD processes are not damaging the graphene. Device quality -The graphene devices were electrically characterized to confirm that they operate as typical graphene devices and to assess their electrical performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since graphene is very sensitive to irradiation from ion and electron beams, [32,[44][45][46][47] it is important to ensure that the FIB, EBID and ALD processes are not damaging the graphene. Device quality -The graphene devices were electrically characterized to confirm that they operate as typical graphene devices and to assess their electrical performance.…”
Section: Resultsmentioning
confidence: 99%
“…[32] The FIB process was optimized to prevent damage to the graphene in the channel by scattered ions as described elsewhere. [32] In the same DualBeam system, the contact pattern seed layers were then deposited by a standard Pt EBID process using MeCpPtMe3 precursor. Typical electron beam settings include an acceleration voltage of 5 kV, beam current of 20 nA and total electron dose of 1.2 nC/m 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of FIB irradiation is known to extend far from the directly irradiated area. [14][15][16] When a FIB is irradiated near a hot-film sensor, it may change the properties of the hot film. Consequently, it is necessary to understand how the electrical properties of hot films are influenced by FIB irradiation to obtain accurate experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main reasons why a FIB exerts an influence far from its directly irradiated area. [15,16] One is the Gaussian distribution of a FIB. Liao et al [15] observed the areas of graphene damaged by a FIB by Raman spectroscopy, and reported that the considerable lateral damage can be attributed to the Gaussian beam shape and unfocused gallium (Ga) ions in the FIB.…”
Section: Introductionmentioning
confidence: 99%